Meningkatkan Inovasi dan Loyalitas Karyawan UMKM - Zulkarnaini Zulkarnaini (Universitas 45 Surabaya, 2025)
Organizational innovation and loyalty are important elements in maintaining the sustainability and effectiveness of a community, including MSME employees. This study aims to analyze the factors that contribute to increasing innovation and loyalty of MSME employees. The research method used is a qualitative approach with observation techniques and in-depth interviews with administrators and active employees of the organization. The results of the study indicate that inspirational leadership, inclusive organizational culture, and active employee involvement in MSME activities are the main factors in increasing innovation and loyalty. In addition, creative programs that are in accordance with employee interests and needs can increase participation and a sense of belonging to the organization. Thus, the application of observation and interview-based strategies can provide a deeper understanding of organizational dynamics and help in designing more effective programs.